What undermines healthy habits with regard to physical activity and food? Voices of adolescents in a disadvantaged community. (18th December 2017) - Jonsson, Linus; Larsson, Christel; Berg, Christina; Korp, Peter; Lindgren, Eva-Carin
ABSTRACT: This study aimed to illuminate factors that undermine the healthy habits of adolescents from a multicultural community with low socioeconomic status (S.E.S.) in Sweden with regard to physical activity (P.A.) and food, as stated in their own voices. Adolescents ( n = 53, 12–13 y/o) were recruited from one school situated in a multicultural community characterized by low S.E.S. Embracing an interpretive approach, 10 focus-group interviews were conducted to produce data for the study. The focus-group interviews were audio recorded, transcribed verbatim, and analysed using qualitative content analysis. The analysis resulted in two major themes: (1) the availability of temptations is large, and support from the surroundings is limited; and (2) norms and demands set the agenda. The adolescents' voices illuminate a profound awareness and the magnitude of tempting screen-based activities as undermining their P.A. and healthy food habits. Moreover, several gender boundaries were highlighted as undermining girls' P.A. and healthy food habits. The adolescents' stories illuminated that it is difficult for them, within their environment, to establish healthy habits with regard to P.A. and food. To facilitate the adolescents' healthy habits, we suggest that support from family, friends, the school, and society at large is essential.